2018
DOI: 10.1042/bsr20180365
|View full text |Cite
|
Sign up to set email alerts
|

Association between long non-coding RNA polymorphisms and cancer risk: a meta-analysis

Abstract: Several studies have suggested that long non-coding RNA (lncRNA) gene polymorphisms are associated with cancer risk. In the present study, we conducted a meta-analysis related to studies on the association between lncRNA single-nucleotide polymorphisms (SNPs) and the overall risk of cancer. A total of 12 SNPs in five common lncRNA genes were finally included in the meta-analysis. In the lncRNA antisense non-coding RNA (ncRNA) in the INK4 locus (ANRIL), the rs1333048 A/C, rs4977574 A/G, and rs10757278 A/G polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 43 publications
(39 reference statements)
4
46
0
Order By: Relevance
“…In addition, MALAT1 induced EMT and suppressed cell apoptosis via Wnt/β-catenin signaling pathway [40]. Consistent with one previous meta-analysis including 2 studies for rs619586 [41], we found it was associated with decreased cancer risk in all populations. Nonetheless, no association was found between rs619586 and melanoma risk [29].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, MALAT1 induced EMT and suppressed cell apoptosis via Wnt/β-catenin signaling pathway [40]. Consistent with one previous meta-analysis including 2 studies for rs619586 [41], we found it was associated with decreased cancer risk in all populations. Nonetheless, no association was found between rs619586 and melanoma risk [29].…”
Section: Discussionsupporting
confidence: 91%
“…Although few examples of lncRNAs are currently used in clinical practice, the list of potential biomarkers is large for almost all cancer types (Table ). For example, there are numerous descriptions associating polymorphisms, mainly single nucleotide polymorphisms (SNPs), with potential predictive biomarkers for the risk of cancer, including SNPs in ANRIL , MALAT1 , HOXA , HULC and PRNCR1 …”
Section: Lncrnas With Potential For Clinical Applicationmentioning
confidence: 99%
“…For example, there are numerous descriptions associating polymorphisms, mainly single nucleotide polymorphisms (SNPs), with potential predictive biomarkers for the risk of cancer, including SNPs in ANRIL, MALAT1, HOXA, HULC and PRNCR1. 162,163 Considering RNA expression, several lncRNAs were associated with stage, prognosis and chemotherapy resistance in many different tumor types. 164 Beyond the detection of lncRNAs deregulated in tumor tissues, these molecules have been analyzed in body fluids (whole blood, plasma, urine, gastric juice and saliva) ( Table 2), suggesting possible non-invasive and more convenient methods that are easily clinically acceptable.…”
Section: Reprogramming Of Energy Metabolismmentioning
confidence: 99%
“…The expression of the same lncRNA transcripts varies by different health conditions, age, tissues, even cells, which can indicate their potential as possible biomarkers and be predictive of diagnosis and prognosis of diseases . Enormous studies have proven that lncRNAs were associated with tumorgenesis, progression, metastasis, and drug resistance, functioning as oncogenes, tumor suppressor genes, or both, involving in shaping multiple biological characteristics of cancer at transcriptional, posttranscriptional, and epigenetic levels . In addition, the abnormal expression levels of different lncRNAs with oncogenic and tumor suppressor functions have been frequently found in the development of BC .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Enormous studies have proven that lncRNAs were associated with tumorgenesis, progression, metastasis, and drug resistance, functioning as oncogenes, tumor suppressor genes, or both, involving in shaping multiple biological characteristics of cancer at transcriptional, posttranscriptional, and epigenetic levels. [10][11][12] In addition, the abnormal expression levels of different lncRNAs with oncogenic and tumor suppressor functions have been frequently found in the development of BC. 13 Particularly, adverse rules of miRNAs-sponging ln-cRNAs, involved in ceRNA networks (ceRNETs), have been shown in BC.…”
Section: Introductionmentioning
confidence: 99%